eInclusion @ Cyprus Universities : Provision and Web Accessibility - Mavrou, Katerina; Zaphiris, Panayiotis; Michailidou, Eleni (My University, 2012)
This paper presents part of a work-in-progress that aims to discuss issues of accessibility in higher education regarding equal opportunities in the use and access of information and technology for students with disabilities in Cyprus. All Cypriot university Websites have been examined using accessibility evaluation techniques and the provisions made by the higher education officers for equal access to their university websites have been reviewed. The results showed that all university pages show accessibility problems, with the public ones having the least errors. With respect to provisions, results showed that internal regulations and policy of universities did not include any specific provisions for web or other technology accessibility.
Keywords: Higher education; Web accessibility; Evaluation; Provision